The Effect Of The Holy Qurʾan On Arabic Rhetoric: Illumination At The Path And The Fate - Nawaya, Fehmieh Rafik; Burhan, Ahmad S.; Hajji, Abdulaziz E. (Ijaz Arabi Journal of Arabic Learning, 2023)
Arabic Rhetoric is one of the featured Arabic language sciences. This research aimed at defining the path of Arabic Rhetoric, observing the influence of the Holy Qur’an on rhetorical studies, and predicting the future. The descriptive methodology was followed as the development of this science had been tracked since its inception until now. The results: 1. Arabic Rhetoric science has undergone methodological and procedural transformations during its development path. Along with positive transformations, some errors have happened. 2. The Holy Qur’an is the guardian that has protected the Rhetoric science path from deviation. It is the role model that the scientists engaged in Rhetoric science have depended on and cited. 3. Future efforts are still needed to purify the rhetorical approach. The desired development will be achieved when Qur’anic usage in the rhetorical field is fully invested.